SAT0708-HPR DEVELOPING AN ALLIED HEALTH CORE OUTCOME SET FOR PAEDIATRIC RHEUMATOLOGY MUSCULOSKELETAL CONDITIONS. (June 2019) - Cuthbert, Verna; Harbottle, Victoria; Potts, Ellie
Abstract : Background: Musculoskeletal (MSK) conditions are prevalent within the general population, including children and young people (CYP) with MSK pain. There is evidence that MSK pain in CYP is an antecedent of adult MSK pain. Paediatric Rheumatology Allied Health Professionals (PRAHPs) are well placed to manage these CYP, but there is no current standardisation in treatment, services or outcomes. Objectives: To develop a core outcome measure set for clinical use by PRAHPs to facilitate national collaboration and standardisation of care. Methods: A modified Nominal Group technique study was undertaken by an expert* panel of PRAHP's working in 8 Tertiary Paediatric and Adolescent UK centres. Literature search and presentation of findings informed expert panel discussion with particular reference to the following criteria: paediatric population specific, ease of clinical use, cost, general availability to clinicians, reliability, validity, length to administer/perform and previous research use. Expert panel discussion and ranking identified eight domains. A survey was sent to the 12 members of the expert panel asking participants to choose two measures or none, based on criteria above. Consensus was pre-determined as agreement between experts of 60% or more. Results: Survey response rate was 83% with consensus achieved for 6 outcome measures- see table. Consensus could not be reached for hand function, sleep and goal-setting in part due to the large number of measures and variation in use, lack of paediatric specific measures, length of time taken to administer or costs involved. Psychological measures were not included within the scope of this work, but would be a valuable future addition. Conclusion: This study informs a pilot outcome measure set for PRAHPs in clinical settings when time, space, money and ease of use are paramount. Acknowledgement: Members of Expert PRAHP panel and valuable feedback from Dr Kate Armon, Dr Joyce Davidson & Dr Janet McDonagh Disclosure of Interests: None declared